(untitled) - Ferris, Kerry (New York, 2008)
The first “participatory” introduction to sociology textbook, The Real World is the perfect choice for today’s students. With a clever mix of popular culture, everyday life, and extensive student activities, The Real World fully realizes sociology’s unique ability to stimulate students intellectually as well as resonate with them personally
Keywords: Sociology,Popular culture,Xã hội học,Văn hóa xã hội; United States,Hoa Kỳ